Value Identification of Under-age Marriage among Sasak People: A Literature Review - Andriyan, Ade; Suryanto, Suryanto; Herdiana, Ike (Jurnal Pendidikan Ilmu Sosial, 2021)
This study aims to describe the further concept of under-age marriage among the Sasak people. This is important considering that early marriage is a social phenomenon that still occurs in many parts of Indonesia, including on the Lombok island, Indonesia. This high rate of marriage occurs in both urban and rural areas with a variety of social, economic and cultural backgrounds. This study uses a qualitative approach with literature study methods. The data collection technique was carried out by reviewing the official website of Google Scholar, Research Gate, Science Direct, and trusted online media sites. The results of this study indicate that early marriage is marriage under the proper age and not physically and mentally ready to carry out marriage. Early marriages occur due to the encouragement of various factors including social, economic, educational and cultural factors. The impact of early marriage, among others, causes children to drop out of school, instability in building a family, the occurrence of domestic violence (KDRT), and women's subordination which is then summarized based on the economic, social, health and psychological impacts both in the short and long term.